2018
DOI: 10.1024/0300-9831/a000268
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol, Ergosterol, and Cholesterol Enhance the Antibiotic Activity of Drugs

Abstract: Abstract. Background: This is the first report demonstrating the antibiotic-modifying activity of cholecalciferol. Aim: In this study, cholecalciferol was evaluated against multiresistant strains of Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. Methods: The antibacterial and modulatory effects of cholecalciferol, ergosterol, and cholesterol (8–512 μg/mL) were evaluated by microdilution assay against multiresistant bacterial strains. Results: Cholecalciferol, when combined with aminoglyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Vitamin D, for instance, displayed antibacterial effects against Porphyromonas gingivalis [36], Streptococcus mutans [37], and Helicobacter pylori [38]. In addition, synergistic antimicrobial effects of vitamin D in combination with distinct antibiotic compounds directed against MDR strains of P. aeruginosa and S. aureus have also been described [39]. Furthermore, in an acute campylobacteriosis model, vitamin D application could sufficiently dampen pro-inflammatory immune responses upon peroral infection of mice with the enteropathogen Campylobacter jejuni [34].…”
Section: Vitamin E As a Promising Candidate Molecule In The Combat Ofmentioning
confidence: 99%
“…Vitamin D, for instance, displayed antibacterial effects against Porphyromonas gingivalis [36], Streptococcus mutans [37], and Helicobacter pylori [38]. In addition, synergistic antimicrobial effects of vitamin D in combination with distinct antibiotic compounds directed against MDR strains of P. aeruginosa and S. aureus have also been described [39]. Furthermore, in an acute campylobacteriosis model, vitamin D application could sufficiently dampen pro-inflammatory immune responses upon peroral infection of mice with the enteropathogen Campylobacter jejuni [34].…”
Section: Vitamin E As a Promising Candidate Molecule In The Combat Ofmentioning
confidence: 99%
“…Previous reports documented health-beneficial effects of vitamins in general [4, 5, 6, 7, 8, 9, 10, 11, 12]. Among these, vitamin D has been shown to alleviate several morbidities, including bacterial infections caused by Mycobacterium tuberculosis and S. aureus [8, 18, 19, 20, 21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports documented health-beneficial effects of vitamins in general [4, 5, 6, 7, 8, 9, 10, 11, 12]. Among these, vitamin D has been shown to alleviate several morbidities, including bacterial infections caused by Mycobacterium tuberculosis and S. aureus [8, 18, 19, 20, 21, 22]. In addition, vitamin D has been shown to support clearance of P. aeruginosa by macrophages [8, 23] and to exert direct bactericidal activity against Helicobacter pylori [6, 7, 24], as well as against Streptococcus mutans [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune cells contain all the machinery required to synthesize and respond to VitD3, and this machinery is enhanced by challenge to the immune system (Gombart, 2009). Notably, VitD3 has been shown to support the clearance of Pseudomonas aeruginosa (P. aeruginosa) by use of macrophages (Nouari et al, 2016;Andrade et al, 2018) and to exert direct bactericidal activity against Streptococcus mutants (Saputo et al, 2018). In vitro studies have revealed that VitD3 application can inhibit virulence factor expression in Porphyromonas gingivalis and halt bacterial growth (Grenier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%